FAKTOR YANG MEMPENGARUHI KEPATUHAN PENDERITA TBC UNTUK MINUM OBAT ANTI TUBERKULOSIS ( Factors contributing patiens’ compliance with Anti Tuberculostatic Drug Therapy) - Lestari, Siti Lestari; Hana M, Choiril (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2006)
The overall aim of the study was to wxplore facilitating and obstructing factor for compliance with TB drug therapy. TBC is an infectious disease caused by mycobacterium Tuberculosis. It is still a health problem in the world, especially in development country. In Indonesia, there have been approximately 538.000 case per year of new active TBC with the mortality was 140.000. seventy five percent (75%) of the case suffered productive group (15 – 50 years old). Furthermore, TB is the third mortality after cardiovasculair and Upper Respiratory Infection ( Dep Kes RI, 2002). These statistic indicate that TB is still major health problem in Indonesia. Currently, management of TBC is conducted by all health care services including, public and private hospital, and community health center. The management of TB using Antituberculosa drug is provided by the Indonesia government. It is free and guarantee. The length of therapy needed is around 6-8 months, tend to cause patient’s uncomplaint, therefore leading to treatment failure and development of resistant strain. For this reason, it is important yo explore what factor contributing patient’s compliance for Tuberculostatic drug therapy. Data were collected by indepth interview from 10 respondents. A content analyses technique were used to analyses the data. The patient emphazed motivation for healing, support from family, and health education as facilitating factor. Other perceived promoting factors included supervision from Pengawas Minum Obat (PMO) and fear to spread the disease to their family. Examples of obstructing factors were the length of therapy and when they suffered from other disease. Key word : patient’s complain, Antituberculosis drug.